Conceptual patterns for water resources information systems - Iturraspe, Rodolfo Javier (2003)
Water Resources Information Systems (WRIS) present different types of problems during the data storage and analysis phases, related with the complex nature of the environmental data spacio-temporal phenomena. There are many questions to deal with, such as geographic representation of environmental variables, large time- series management,measurements and observations related with different hydrologic phenomena recording and the integration of simulations models to information systems. Conceptual models allow us to understand and simplify problems in a specific domain. These problems can be expressed through analysis patterns, which reflect conceptual structures of an application domain speeding up the development of the abstract analysis model. This model will be able to capture the main requirements from real world problems. This type of patterns, are used in the present paper to define conceptual microarchitectures that allow the appropriate representation of environmental information in WRIS. Accordingly, the physic domain environmental objects are initially identified and an architecture style is defined, allowing this way the integration of WRIS with another interacting systems. The representation of the hydrological phenomena spatial component, is made by means of the conceptual Framework GeoFrame specialization.